The effect of "Bumil Waspada" to prevent hypertension - Aji, Hanifah Sarah Nur Laila; Siti Nurhidayati; Luluk Fajria Maulida; Niken Bayu Argaheni; Noviyati Rahardjo Putri (International Journal of Health Science and Technology, 2024)
Deficits in self-care skills such as liking to eat fried foods, foods high in fat and salt, lack of rest, and laziness to exercise are the causes of hypertension in pregnancy. Hypertension in pregnancy can be overcome by providing educational assistance to high-risk groups in the form of preventive measures such as a diet low in sodium and fat, walking, consuming calcium supplements, monitoring weight gain, and hydrotherapy that is a member of "Bumil Waspada". The purpose of this study is to determine the effect of "Bumil Waspada" on the ability to take care of herself in pregnant women with risk factors for hypertension. The design of this study used one group pretest-postest with purposive sampling, namely pregnant women with risk factors for hypertension in the working area of the Selogiri Health Center, Wonogiri Regency, totalling 47 people. The media used are educational texts with pictures and questionnaires as instruments. Bivariate analysis uses the Wilcoxon test. The study results showed an increase in self-care ability in the "good" category from 1 person to 23 people and another 24 people in the "adequate" category. The results of the Wilcoxon test showed a value of Z > z and p-value = 0.000 < 0.05, so there was a significant average difference between before and after the intervention. "Bumil Waspada" affects the ability to take care of herself in pregnant women with risk factors for hypertension.